PENGARUH PEMBERIAN EKSTRAK BUAH PIDADA MERAH (SONNERATIA CASEOLARIS (L.) ENGL.) TERHADAP KADAR KOLESTEROL LDL PADA TIKUS WISTAR DIABETIK - Monicha Salsabila (2023)
Dyslipidemia in diabetes mellitus is a risk of atherosclerosis that causes cardiovascular disease which has the highest prevalence of death. Lifestyle changes, pharmacological or supportive therapy can be used to treat dyslipidemia. The aim of the study was to find out how Wistar rats' LDL cholesterol was affected by Red Pidada fruit extract. The design was a post-test only control group design, a sample of 30 male Wistar rats weighing 150-200 grams and aged 2-3 months were selected by simple random sampling from PT. Biopharma Bandung. Rats were divided into groups of standard feed and distilled water (K1), high-fat feed and alloxan (K2), high-fat feed, alloxan and simvastatin (K3), high-fat feed, alloxan and Red Pidada fruit extract (200;400;800) mg/kgBB (K4;K5;K6). After given a high-fat diet for 28 days, rats were induced with alloxan 125 mg/kg BW after fasting for 8-10 hours, blood glucose levels were checked 48 hours later. Giving treatment for 14 days. After dissecting and injecting them with ketamine xylazine, blood was collected and centrifuged in EDTA tubes. Measure LDL cholesterol levels using a spectrophotometer with a wavelength of 570 nm. The One-Way ANOVA test showed the effect of Red Pidada fruit extract on LDL cholesterol levels (p=0.004). Bonferroni post hoc test Red Pidada fruit extract 400mg/KgBW reduced LDL cholesterol almost the same as simvastatin (p=1,000) close to normal values. Red Pidada fruit can be used as a supportive therapy for dyslipidemia because it contains flavonoids and alkaloids and improve LDL cholesterol by inhibiting HMG CoA reductase.